Social work, poverty, and child welfare interventions - Morris, Kate; Mason, Will; Bywaters, Paul; Featherstone, Brid; Daniel, Brigid; Brady, Geraldine; Bunting, Lisa; Hooper, Jade; Mirza, Nughmana; Scourfield, Jonathan; Webb, Calum (Child & family social work, 2018)
The relationship between children's material circumstances and child abuse and neglect raises a series of questions for policy, practice, and practitioners. Children and families in poverty are significantly more likely to be the subject of state intervention. This article, based on a unique mixed‐methods study of social work interventions and the influence of poverty, highlights a narrative from practitioners that argues that, as many poor families do not harm their children, it is stigmatizing to discuss a link between poverty and child abuse and neglect. The data reveal that poverty has become invisible in practice, in part justified by avoiding stigma but also because of a lack of up‐to‐date research knowledge and investment by some social workers in an “underclass” discourse. We argue, in light of the evidence that poverty is a contributory factor in the risk of harm, that it is vital that social work engages with the evidence and in critical reflection about intervening in the context of poverty. We identify the need for fresh approaches to the harms children and families face in order to support practices that engage confidently with the consequences of poverty and deprivation.